Ten years in: APOL1 reaches beyond the kidney. Issue 4 (July 2019) - Waitzman, Joshua S.; Lin, Jennie
Abstract : Purpose of review: APOL1 nephropathy risk variants drive most of the excess risk of chronic kidney disease (CKD) seen in African Americans, but whether the same risk variants account for excess cardiovascular risk remains unclear. This mini-review highlights the controversies in the APOL1 cardiovascular field. Recent findings: In the past 10 years, our understanding of how APOL1 risk variants contribute to renal cytotoxicity has increased. Some of the proposed mechanisms for kidney disease are biologically plausible for cells and tissues relevant to cardiovascular disease (CVD), but cardiovascular studies published since 2014 have reported conflicting results regarding APOL1 risk variant association with cardiovascular outcomes. In the past year, several studies have also contributed conflicting results from different types of study populations. Summary: Heterogeneity in study population and study design has led to differing reports on the role of APOL1 nephropathy risk variants in CVD. Without consistently validated associations between these risk variants and CVD, mechanistic studies for APOL1's role in cardiovascular biology lag behind.